Proceedings of the 3rd Annual International Conference on Mechanics and Mechanical Engineering (MME 2016) 2017
DOI: 10.2991/mme-16.2017.78
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucose on the Crystallization and Thermal Properties of Poly(L-Lactic Acid) Prepared Through Mixed Solution Method

Abstract: Abstract. The blends of PLLA (PLLA) and glucose(Glu) were prepared by mixing PLLA solution and glucose solution with various ratios when PLLA and glucose were respectively dissolved in N,N-dimethyl acetamide to prepare solutions. The structure, thermal properties and crystallinity of PLLA, glucose and PLLA-Glu blends were investigated by Fourier transform infrared spectrometry, differential scanning calorimetry, thermal gravity analysis, X-ray diffraction and polarized optical microscopy. PLLA and glucose in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…On account of the comprehensive effects of the above factors, the T max of sc-PLAG-0.5% was about 262 • C, then the T max of sc-PLAG samples increased steadily with the increase of glucose content in feeding until the glucose content in feeding was 5%. Compared to PLLA-glucose blends [26] and PLA with different processing methods [41], the T b , T max , and T f of all sc-PLAG were lower than those of PLLA-glucose blends and the PLA materials, which indicated that the copolymerization of poly(lactic acid) and glucose and stereocomplex of PLA was more able to promote thermal degradation of PLLA.…”
Section: Samplementioning
confidence: 88%
See 3 more Smart Citations
“…On account of the comprehensive effects of the above factors, the T max of sc-PLAG-0.5% was about 262 • C, then the T max of sc-PLAG samples increased steadily with the increase of glucose content in feeding until the glucose content in feeding was 5%. Compared to PLLA-glucose blends [26] and PLA with different processing methods [41], the T b , T max , and T f of all sc-PLAG were lower than those of PLLA-glucose blends and the PLA materials, which indicated that the copolymerization of poly(lactic acid) and glucose and stereocomplex of PLA was more able to promote thermal degradation of PLLA.…”
Section: Samplementioning
confidence: 88%
“…Compared to PLLA-glucose blends [26] and PLA with different processing methods [41], the Tb, Tmax, and Tf of all sc-PLAG were lower than those of PLLA-glucose blends and the PLA materials, which indicated that the copolymerization of poly(lactic acid) and glucose and stereocomplex of PLA was more able to promote thermal degradation of PLLA.…”
Section: Tga Analysis Of the Thermal Properties Of Sc-plagmentioning
confidence: 89%
See 2 more Smart Citations